1997
DOI: 10.1021/jm960719a
|View full text |Cite
|
Sign up to set email alerts
|

Neuritogenic Effect of Epolactaene Derivatives on Human Neuroblastoma Cells Which Lack High-Affinity Nerve Growth Factor Receptors

Abstract: Neurotrophic factors such as nerve growth factor (NGF) are involved in survival, growth, and differentiation in normal and neoplastic nerve cells. 1,2 At least three receptors bearing tyrosine kinase activity for neurotrophic factors have beeen cloned; 3-5 TRK-A encodes a high-affinity receptor for NGF and also binds neurotrophin-3 (NT-3) and neurotrophin-4/5 (NT-4/5). 6-8 TRK-B encodes a receptor for brain-derived neurotrophic factor (BDNF) and also binds NT-3 and NT-4/5, and TRK-C encodes a receptor for NT-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(34 citation statements)
references
References 26 publications
0
33
0
1
Order By: Relevance
“…1,[8][9][10] They found that epolactaene bound to human Hsp60 and inhibited its chaperone activity. 9,10) Ikekita et al found that 1 induced apoptosis in a human leukemia B cell line, BALL-1.…”
Section: -7)mentioning
confidence: 99%
See 1 more Smart Citation
“…1,[8][9][10] They found that epolactaene bound to human Hsp60 and inhibited its chaperone activity. 9,10) Ikekita et al found that 1 induced apoptosis in a human leukemia B cell line, BALL-1.…”
Section: -7)mentioning
confidence: 99%
“…Treatment of 6 with aqueous HF in CH 3 CN led to desilylation and cyclization to form -angelica lactone (7). Epoxidation of 7 by a modification of Font's procedure 20) gave enantiomerically pure -angelica lactone epoxide (8) in 60% yield and 98% ee (by HPLC). After treatment of 8 with K 2 CO 3 in MeOH, the resulting alcohol was protected as TBS ether 9.…”
Section: Synthesis Of Epolactaenementioning
confidence: 99%
“…MT-21 was synthesized as previously described (Kakeya et al, 1997), solubilized in methanol and used for experiments. Z-Asp-CH 2 -DCB (Z-Asp) was purchased from Peptide Institute, Inc. (Osaka, Japan) and used as an inhibitor with a broad speci®city to various caspases.…”
Section: Chemicalsmentioning
confidence: 99%
“…It is possible that most apoptotic signals including the Fas-mediated signal and the cytotrienin-induced signal activate several pathways for apoptosis in a target cell. Unlike these apoptosis inducers, MT-21 (3-acetyl-4,5-dimethyl-5-octyloxy-3-pyrrolin-2-one), our synthetic apoptosis inducer, activates the signal from caspase-3, MST/Krs to JNK in a rather simple manner (16,17). In the present study, we have investigated the caspase-mediated proteolytic activation of MST/Krs proteins in cytotrienin A-sensitive and -resistant human tumor cell lines.…”
mentioning
confidence: 99%